Understanding the Dynamics between Social Entrepreneurship and Inclusive Growth in Subsistence Marketplaces. (September 2015) - Azmat, Fara; Ferdous, Ahmed Shahriar; Couchman, Paul
This article explores how social entrepreneurs utilize their unique circumstances and resources at a micro level to facilitate the creation of shared value at the meso level, leading to inclusive growth at a macro level in the context of subsistence marketplaces. Drawing from explanatory case studies of two social enterprises—Waste Concern (Bangladesh) and Seven Women (Nepal)—the findings suggest that social entrepreneurs act as bricoleurs to integrate their operant and operand resources in subsistence marketplaces to facilitate inclusive growth. The authors further connect with and extend three discourses of research—social entrepreneurship, social bricolage, and service-dominant logic—to develop a framework providing insights into the "bottom-up" approach, the underlying dynamics of shared value creation, and inclusive growth in subsistence marketplaces by social entrepreneurs. The findings also strengthenDees's (2001) definition of social entrepreneurship, confirming its applicability and relevance in subsistence marketplaces and further extending the theory of social bricolage. The authors discuss the implications of these findings, including tactical interventions aimed at providing better understanding of how social entrepreneurs create value in resource-constrained marketplaces, from a bottom-up perspective.